The Third Sector Delivering Public Services : Developments, Innovations and Challenges - Mullins, David, 1955-; Rees, James, 1978- (Book collections on Project MUSE., 2016)
This edited collection explores areas such as social enterprise, capacity building, volunteering and social value, and charts the historical development of the statethird sector relationship, reviewing the major debates and controversies accompanying recent shifts in that relationship.